Vertical Information System: A Case Study of Civil Servant Teachers’ Data in Manado City - Julyeta P.A. Runtuwene; Irene R.H.T Tangkawarow (Institute of Advanced Engineering and Science, 2017)
Information systems have become important factors in a company, where information systems are useful in providing useful information for the company itself. The information system helps companies implement corporate activities at the beginning of the process until the decision making. In the concept Information system, we know the term of vertical information system, which is another strategy for increasing vertical information capacity. Vertical information system includes the periodic report, written information, and computer-based communications distributed to managers. In this article, discusses the approach in the development of vertical information system which will be preceded by comparison of operational systems, management information systems, and business intelligence systems. We will give explanations about the role in the BI system in an organization, the challenges faced in the implementation of vertical information systems, approaches in vertical information systems, approaches that we choose, and how it implement in civil servant teachers data in Manado City.